Avaliação da qualidade da energia elétrica em um campus universitário - Silva, Laura Chiovato (2014)
The development and expansion of the federal universities throughout the past years, due to the plans of expansion implemented with the funds from REUNI (The program of supporting for the restructuring and expansion of Federal Universities), suggest the necessity of improving the electrical installations of these institutions in order to meet the new power demand in a planned and efficient way. The subject which is related to the growing costs of electrical energy and investments in electrical installations in teaching institutions, faced with its economic relevance, represents, nowadays, an extremely relevant theme. Therefore, currently, it is possible to observe efforts directed to enhance the procedure of quality and efficiency diagnosis of the electrical energy of a campus. Embedded in this context is this dissertation, which is linked to a measurement plan, analysis methods and data comparison with reference values and the use of tools for modeling and computer simulation. This way, the present work presents four different kinds of contribution to the current state-of-the-art. The first contribution is associated to the obtention of typical charge curves and tax modal analysis chart which seem to be most adequate for a university campus. The second contribution is associated to the methodology of data analysis and the installation diagnosis in terms of power quality. As a third contribution of this work, we have the modeling of the electrical system of installation with the use of the ATP (Alternative Transients Program) computer tool. As a final contribution one can highlight the computer modeling and simulation to identify the harmonic contributions both to the local power utility and to the campus installations, together with the point of common coupling. The obtained results show that the methodology in use is very useful in the daily management of the processes associated with the use of the electrical energy in the installations of a university.